IMPLEMENTATION OF DATA MASKING TECHNIQUES FOR CUSTOMER DATA PROTECTION ON E-COMMERCE WEBSITES - Tia Agustina Widyastuti; Yudo Bismo Utomo; Harso Kurniadi, (Journal of Computer Science and Technology (JCS-TECH), 2026)
Customer data security is an important aspect in managing e-commerce websites because such systems store sensitive information such as phone numbers, email addresses, and transaction histories. If not properly protected, this data may lead to breaches and misuse by unauthorized parties. This study aims to implement a data masking technique as a solution for protecting customer data on an e-commerce website. The research method used was Action Research, consisting of planning, action, observation, and evaluation stages. The data masking technique was applied by disguising all sensitive data characters using specific symbols without changing the original data stored in the database. System testing was conducted using Blackbox Testing and User Acceptance Testing (UAT) involving 293 respondents. The results showed that all system features functioned properly, with a UAT score of 85.37%, categorized as very good. This study contributes to the development of information security systems through the application of data masking as a method for protecting customer privacy in website-based digital services. Therefore, the developed system is effective and feasible to be implemented on e-commerce platforms to improve customer data security.